Índice de fluorosis dental y factores asociados en los niños de la Unidad Educativa “ANDOAS DEL SOCORRO” Parroquia Cubijíes, Cantón Riobamba, Provincia de Chimborazo, periodo 2015- 2016 - Lara Mariño, Cristian Ariel (2017)
The purpose of this study is to identify the index of dental fluorosis and associated factors of children in the Unidad Educativa " ANDOAS DEL SOCORRO" parish Cubijies, Riobamba Canton , Chimborazo Province, for this work it was realized the opening of records in 108 children (58 men - 50 women) with their respective reports endorsed by the parents of each of the children to this we realized a check clinical intraoral evaluating the parts dental, to thus recognize the level of severity of fluorosis present in each child, in which we perform statistical tables to know the percentage of fluorosis existing. Also it was taken samples water of daily consumption to assess the level of fluorine in these, taking 5 samples, the first sample was obtained of the slope of the water which is located in the community of Balcashi which has a percentage of 0.96 ppm, the second sample is located in the reservoir in the community of Porlán where we got a percentage of 0.96 ppm which caters to the community of El Socorro and therefore to the educational unit, the third sample it was obtained of the residence of the president of the community of El Socorro in which there is a percentage of 0.97 ppm, the fourth sample it was obtained educational unit of "ANDOAS DEL SOCORRO" in which was found a percentage equal to the home of 0.97 ppm and the fifth sample was obtained of the slope that exists around the community El Socorro, in which we obtained a rate of 2 ppm, which was consumed like daily water and today it is used as reserve water if the water of the reservoir of Porlán missing them.